The impact of self-care training using the teach-back method on health anxiety in patients with coronary artery disease: A randomized controlled clinical trial - Mansoreh Barati; Zahra Amouzeshi; Fahimeh Nikraftar (Journal of Education and Health Promotion)
BACKGROUND: Coronary artery disease (CAD) is the most prevalent heart disease and a leading cause of death among both men and women. It is worth noting that anxiety is highly prevalent among patients with CAD, and it can significantly affect their overall performance and well-being. This study aimed to determine the impact of self-care training, specifically using the teach-back method, on health anxiety in patients with CAD. MATERIALS AND METHODS: In this randomized controlled clinical trial, a total of 50 patients with coronary artery disorders were selected from the coronary care unit of Rasool Hospital in Ferdows City, Iran, in 2022. The participants were randomly assigned to two groups. The intervention group received self-care training based on the teach-back method, which consisted of three individual sessions lasting 30–45 minutes each, conducted over the course of one week. However, the control group received routine care. To collect data, the researchers utilized Salkovskis et al.’s (2002) health anxiety questionnaire. The collected data were analyzed using the Chi-square test, Fisher’s exact test, independent t-test, and paired t-test at a significance level of P < 0.05. RESULTS: Most participants in the control and intervention groups were female. The mean ages of the intervention and control groups were 47.1 ± 12.83 and 48.1 ± 44.81 years, respectively, with no statistically significant difference (P = 0.67). The results indicated that there was a statistically significant difference in the total mean score (P = 0.000) and mean scores of subscales of health anxiety (awareness of bodily sensations or changes (P = 0.001), feared consequences of having an illness (P = 0.001), and worry about health (P = 0.008)) between the two groups. CONCLUSIONS: The self-care training based on the teach-back method reduced health anxiety in patients with CAD. Therefore, it is recommended to incorporate the teach-back method as an educational approach by nursing team to effectively reduce health anxiety in patients with CAD.